METODE PEMBENTUKAN KEPRIBADIAN ISLAMI MENURUT SYAIKH TAQIYUDDIN AN-NABHANI - Gus Din El-Haq; Iwandi Iwandi (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Syaksiyah Islamiyah is an Islamic Personality. In Muslim scientific literature, the concept of Islamic personality has not been widely developed by Muslim scientific thinkers themselves, so this affects the difficulty of applying Islamic personality and methods of formation. Based on this, this paper contains the thoughts of Muslim leader Syaikh Taqiyuddin An-Nabhani about his views and ideas on the concept of Islamic personality and its method of formation. Islamic personality is formed by Islamic aqliyah and nafsiyah Islam. With the method of instilling Islamic aqeedah and tsaqofah Islam and habituation to always be bound by syara law '. Thus, the formation of Islamic personality is done by means of first compiling a curriculum based on Islamic faith, second, making Islamic theology as the basis of the subject matter, and third using the method of talaqqiyan fikriyan in the teaching process.